Prevalence and molecular study of FMD SAT2 serotype in Northern and Central Iraq - AL-Anbagi, Ghazwan; Allawe, Aida B (The Iraqi Journal of Veterinary Medicine, 2026)
In Iraq, foot-and-mouth disease (FMD) remains a significant challenge to most livestock production. Building upon our previous investigation, which reported overall FMDV prevalence and the first successful isolation of the SAT2 serotype in Iraqi cattle, the present study examines the prevalence of FMDV and provides molecular characterization of selected isolates. A total of 100 clinical samples collected from cattle across five provinces during the July 2023– October 2024 outbreak were analyzed. Using RT-qPCR, 85% (85/100) was positive for the 3D gene, and 35.3% (30/85) of these were positive for the SAT2-specific 1D gene, and there was no significant provincial differences observed in the detection of either gene. Vesicular fluid exhibited a 100% positivity rate for the 1D gene and was significantly higher than the 27.6% positivity in tongue epithelial tissue (P < 0.0001). Logistic regression analysis confirmed lower odds of detecting the 1D gene compared with the 3D gene across all provinces (P < 0.05). Three isolates were sequenced: one 3D-positive sample and two 1D-positive samples. Phylogenetic analysis of the 3D and 1D regions demonstrated clustering within SAT2, showing close relationships to strains circulating in Western Asia and Eastern Africa. This study provides the province-level overview of SAT2 distribution in Iraq and molecular evidence supporting the regional evolution of the circulating strain, emphasizing the need for continued surveillance and updated vaccination strategies‎‎‎.